How Work Intensification Relates to Organization-Level Safety Performance: The Mediating Roles of Safety Climate, Safety Motivation, and Safety Knowledge - Bunner, Johanna; Prem, Roman; Korunka, Christian (Frontiers in Psychology, 2018)
Recent changes in the world of work have led to increased job demands with subsequent effects on occupational safety. Although work intensification has been linked to detrimental safety behavior and more accidents, there is so far, no sufficient explanation for this relationship. This paper investigates the mediating roles of safety climate, safety motivation, and safety knowledge in the relationships of work intensification with components of safety performance at an organizational level. Safety engineers and managers from 122 Austrian high-accident companies participated in a cross-sectional survey. In line with our hypotheses, work intensification negatively related to both components of safety performance: safety compliance and safety participation. The results of a serial multiple mediation analysis further revealed safety climate and safety motivation to be serial mediators of the relationship between work intensification and safety performance. Unexpectedly, safety knowledge and safety climate only serially mediated the relationship between work intensification and safety compliance, but not the relationship between work intensification and safety participation. This study provides evidence for the detrimental effect of work intensification on safety performance across organizations. Additionally, this study offers an explanation as to how work intensification affects safety performance, enabling practitioners to protect their occupational safety procedures and policies from work intensification.